2010
DOI: 10.1149/1.3364794
|View full text |Cite
|
Sign up to set email alerts
|

Nanotubes of Core/Shell Cu/Cu[sub 2]O as Anode Materials for Li-Ion Rechargeable Batteries

Abstract: A direct electrodeposition technique for Cu nanotube array fabrication and the subsequent conversion of the deposited Cu into Cu2O was developed. The Cu2O nanotube arrays showed high capacity, cyclability, and rate capability. The cycling performance of the Cu2O nanotubes showed a high level of structural integrity with capacity retention even after 94 cycles when cycled at 1C to 3C rates. The enhanced electrochemical performance of the Cu2O nanotubes came from a high surface area, electrolyte access, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 19 publications
0
27
0
Order By: Relevance
“…• Nanoscale active materials with improved electronic conductivity or core/shell structures [48] to facilitate high rate solid-state lithium ion transport.…”
Section: Energy Sources and Power Managementmentioning
confidence: 99%
“…• Nanoscale active materials with improved electronic conductivity or core/shell structures [48] to facilitate high rate solid-state lithium ion transport.…”
Section: Energy Sources and Power Managementmentioning
confidence: 99%
“…[20][21][22] Many studies have reported that electrode nanomaterials with specific morphologies exhibit excellent electrochemical performance in LIBs. [23][24][25][26][27][28][29][30][31] Herein, we synthesized Cu 2 O nanostructure anodes with different morphologies by adopting a reducing agent with and without polyvinylpyrrolidone (PVP) as a surfactant. The electrochemical performances of cubic and octahedral Cu 2 O with {100} and {111} facets, respectively, were studied as anode materials for LIBs.…”
Section: Introductionmentioning
confidence: 99%
“…Cuprous oxide (Cu 2 O) is a well-known p-type semiconductor and has a direct small bandgap of 2.2 eV, which endows it promising applications in solar energy conversion [12], as an electrode for lithium-ion batteries [13], gas sensors [14], and photocatalytic degradation of organic pollutants and decomposition of water into O 2 and H 2 under visible light [15-17]. So far, great efforts have been devoted to the synthesis of cuprous oxide with different shapes and sizes.…”
Section: Introductionmentioning
confidence: 99%